2021
DOI: 10.1111/joa.13506
|View full text |Cite
|
Sign up to set email alerts
|

Craniovascular traits and braincase morphology in craniosynostotic human skulls

Abstract: In the human cranium, several vascular networks leave imprints in the endocranial surface or create canals in the bone wall (Píšová et al., 2017;Rangel de Lázaro et al., 2018). Such osteological features, here termed craniovascular traits, provide indirect evidence of vascular patterns when only bone remains are available, such as in bioarchaeology, paleontology, and forensic science. Two vascular systems are imprinted in the endocranial table of the skull, specifically the middle meningeal artery (MMA) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…Jeevan et al, 2008;Rich et al, 2003;Rollins et al, 2000;Taylor et al, 2001;Tokumaru et al, 1996). Signs of elevated intracranial pressure and vascular changes have also been observed in osteological CS samples (Eisová et al, 2021;O'Loughlin, 1996;Weber et al, 2008).…”
Section: Research Highlightsmentioning
confidence: 81%
See 4 more Smart Citations
“…Jeevan et al, 2008;Rich et al, 2003;Rollins et al, 2000;Taylor et al, 2001;Tokumaru et al, 1996). Signs of elevated intracranial pressure and vascular changes have also been observed in osteological CS samples (Eisová et al, 2021;O'Loughlin, 1996;Weber et al, 2008).…”
Section: Research Highlightsmentioning
confidence: 81%
“…Clinical studies provide evidence of the abnormal development of vascular systems in CS, such as stenosis, occlusion or absence of the dural venous sinuses, presence of collateral circulation via emissary veins, narrowing of jugular foramina, jugular vein obstruction, increased volume of CSF, and persistent occipito‐marginal sinuses (Blaser et al, 2015; Copeland et al, 2018; Florisson et al, 2015; Ghali et al, 2019; Hayward, 2005; Jeevan et al, 2008; Rich et al, 2003; Rollins et al, 2000; Taylor et al, 2001; Tokumaru et al, 1996). In fact, our last study showed that in CS the craniovascular traits related to the dural venous sinuses and the emissary veins display altered venous morphology (deeper imprints, presence of enlarged occipito‐marginal sinuses, enlarged emissary foramina, and sometimes atypically narrow jugular foramina) that is probably associated with increased intracranial pressure and venous hypertension (Eisová et al, 2021). The DV directly communicate with both emissary veins and dural venous sinuses, and thus any alteration of one network might influence the others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations